Barriers to ecosystem restoration after clearing invasive Acacia species in the South African fynbos : soil legacy effects, secondary invaders and weedy native species - Nsikani, Mlungele Mlungisi (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.